Linalool as a Therapeutic and Medicinal Tool in Depression Treatment: A Review - dos Santos, Éverton R. Q.; Maia, José Guilherme S.; Fontes-Júnior, Enéas A.; do Socorro Ferraz Maia, Cristiane (Current Neuropharmacology, 2022)
Depression is a prevalent disease worldwide, limiting psychosocial functioning and thequality of life. Linalool is the main constituent of some essential oils from aromatic plants, representing about 70% of these volatile concentrates. Evidence of the linalool activity on the central nervous system, mainly acting as an antidepressant agent, is increasingly abundant. This review aimed to extend the knowledge of linalool's antidepressant action mechanisms, which is fundamental for future research, intending to highlight this natural compound as a new antidepressant phytomedication. A critical analysis is proposed here with probable hypotheses of the synergic mechanisms that support the evidence of antidepressant effects of the linalool. The literature search has been conducted in databases for published scientific articles before December 2020, using relevant keywords. Several pieces of evidence point to the anticonvulsant, sedative, and anxiolytic actions. In addition to these activities, other studies have revealed that linalool acts on the monoaminergic and neuroendocrine systems, inflammatory process, oxidative stress, and neurotrophic factors, such as BDNF, resulting in considerable advances in the knowledge of the etiology of depression. In this context, linalool emerges as a promising bioactive compound in the therapeutic arsenal, capable of interacting with numerous pathophysiological factors and acting on several targets. This review claims to contribute to future studies, highlighting the gaps in the linalool knowledge, such as its kinetics, doses, routes of administration, and multiple targets of interaction, to clarify its antidepressant activity.
Keywords: essential oils